The impact of learners' spatial capacity and world views on their spatial conceptualisation: a case study - Schäfer, Marc (Curtin University, 2003)
This multi-sited case study aims to explore spatial capacity through pen-and-paper and hands-on activity tests, and explore world view perceptions of space in an attempt to show that spatial conceptualisation is a rich and complex blend of spatial capacity and world view. This study is oriented in a interpretive-naturalistic paradigm and characterised by multi-dimensional quantitative and qualitative methods. The research, set in five secondary schools in the Eastern Cape, was carried out with 32 Grade 11 learners and was designed around seven stages. This study attempts to understand spatial conceptualisation by recognising that all learners have epistemological macrostructures (world views) that shape their perceptions of the world in general and of space in particular. The main contention of this study is that spatial conceptualisation cannot be understood in isolation, through studying achievements on traditional pen-and-paper tests only. A comprehensive understanding of an individual's spatial conceptualisation involves the recognition of hands-on skills and world views as well. Spatial capacity, defined here in terms of spatial visualisation and orientation constructs, was explored through a pen-and-paper and a hands-on activity test. The results show only a weak to moderate correlation between the two tests, suggesting that performance in a traditional pen-and-paper test was not necessarily a good predictor for performance in a hands-on activity-based test. The investigation of world views was underpinned by a logico-structuralist process centred in conversations around nine bi-polar themes. Through a process of content- and meta- analyses involving the participation of a validation team, world-view profiles were established.In terms of the applied pen-and-paper test which explored spatial capacity, this study confirms males' dominance in all spatial tasks, particularly in three-dimensional problems. This was also found to be true for learners from the participating rural school and for those from disadvantaged socio-economic backgrounds. In the hands-on activity test, however, the study revealed no observable gender difference in favour of the males, except for items that were characterised by the spatial orientation construct. Both the participating rural and township schools performed poorly in items characterized by the spatial visualisation and orientation construct compared to the other participating schools. Although participants from the rural and township schools found it difficult to articulate their world views in depth, the world-view perspectives of space of this sample reveal rich and complex profiles that are similar across all the schools. Despite leaning towards a Newtonian division of absolute and relative space and containing strong religious elements, this sample generally views space as mysterious, infinite and somewhat obscure. It often refers to space in Kantian ideas and related space in terms of subjective feelings. Females in particular, refer to their own `space bubble', for example. Out of the world-view profile analysis, a meta-analysis was conducted which explored thinking skills in terms of capacity to abstract, to be insightful, deal with complex issues, engage critically, and be imaginative.This reveals that for this case, females were rated on a higher level than their male counterparts for their capacity to abstract and be complex (the capacity to identify related parts and to deal with composites), whereas males rated higher for showing insight, being imaginative, and being critical. Although there appear to be high correlations between the various tests, meta-levels and school performance for some of the participants, the same cannot be said for the sample as a whole. The world-view aspect of this study reveals a rich, often complex, understanding of space, strengthening the notion that world views are integral to a learner's cognition process.